KHULAFÂ RÂSYIDÛN : Sistem Kepemerintahan di Masa ‘Utsmân bin Affân dan ‘Ali bin Abi Thâlib - Sunandar , Sunandar; Tomi, Tomi (ADISAM PUBLISHER, 2024)
This research explores the leadership system of the Khulafâ al-Râsyidûn, particularly during the time of ‘Uthman ibn Affan and ‘Ali ibn Abi Talib. Islam, in its early emergence, faced significant challenges, including physical warfare to strengthen the Islamic state. The study employs a literature review or library research method to analyze the leadership of Khulafâ al-Râsyidûn, especially focusing on ‘Uthman and ‘Ali. It adopts a historical approach to present the development of the leadership system during a specific period in Islamic history. In this context, library research provides an in-depth insight into the conflicts and dynamics that occurred during the leadership of Khulafâ al-Râsyidûn, aiding in understanding the historical context of Islam. The initial phase of ‘Uthman's leadership was characterized by amicable relations with the Quraysh tribe. However, the second phase led to dissatisfaction due to nepotistic policies. Public protests escalated, and ‘Uthman was eventually assassinated. During this period, conflicts extended beyond the selection of Prophet Muhammad's successor, encompassing internal conflicts within the Muslim community. The phases of ‘Uthman's leadership reflect changes in the relationship between society and the government, as well as the determination of internal policies.